2006
DOI: 10.1002/ps.1183
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analysis of a chlorfenapyr‐selected resistant strain of Tetranychus urticae Koch

Abstract: Tetranychus urticae Koch has recently developed resistance to chlorfenapyr in Australia and Japan, but no attempt has yet been made to describe the biochemical mechanisms involved in chlorfenapyr resistance. In this study a laboratory-selected chlorfenapyr-resistant strain was investigated. Resistance to chlorfenapyr was associated with a strong increase in esterase activity and P450 mono-oxygenase (MO) activity but a decrease in 3,3',5,5'-tetramethylbenzidine (TMBZ) peroxidation activity. Differences in ester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 21 publications
1
56
2
3
Order By: Relevance
“…The optical density (OD) was continuously measured at 340 nm every 15 sec for a total of 10 min on Synergy HTX plate reader. The specific GST activity was calculated to nmol CDNB conjugation/min/mg protein using experimentally derived “extinction coefficients” of 5.3 mM -1 cm -1 [37]. …”
Section: Methodsmentioning
confidence: 99%
“…The optical density (OD) was continuously measured at 340 nm every 15 sec for a total of 10 min on Synergy HTX plate reader. The specific GST activity was calculated to nmol CDNB conjugation/min/mg protein using experimentally derived “extinction coefficients” of 5.3 mM -1 cm -1 [37]. …”
Section: Methodsmentioning
confidence: 99%
“…However, although high resistance (41000-fold) to some of these acaricides has been documented (Goka, 1998;Devine et al, 2001;Stumpf and Nauen, 2001;Van Leeuwen et al, 2004), no maternal inherited resistance has been found. This probably indicates that either the target protein of these acaricides is encoded by the nucleus or resistance was due to metabolic degradation as demonstrated for pyridaben and chlorfenapyr by employing synergists known to inhibit detoxification enzymes, such as mono-oxygenases and esterases Van Leeuwen et al, 2006). When synergists known to inhibit oxidative and hydrolytic detoxification enzymes were applied to females of strain BR-VL prior to bifenazate treatment, no increase in susceptibility was detected.…”
Section: Article In Pressmentioning
confidence: 97%
“…As for mechanisms of resistance to acaricides with new modes of action (e.g. abamectin, fenpyroximate, chlorphenapyr, METI-acaricides, spirodiclofen) enhanced detoxification in T. urticae strains has been reported (Devine et al 2001;Nauen 2001, 2002;Kim et al 2004a, b;Van Leeuwen et al 2006;Van Pottelberge et al 2008. Other detoxification or target enzymes such as esterase, cytochrome P450-monooxygenase and glutathione S-transferase may also play a role in metabolizing certain acaricides in T. urticae (Yang et al 2001).…”
Section: Introductionmentioning
confidence: 95%